Synthesis of Some 2-Oxazolidinones in Mild Conditions - Bratulescu, George (Asian Journal of Chemistry, 2010)
One step efficient protocol for the synthesis of 2-oxazolidinones in paste chemical medium is described under microwave activation with 80 % yield.